Transient shrinkage behavior of wustite-centered binary/ternary/quaternary/quinary-component oxide packed beds in a reducing atmosphere up to 1773 K. Issue 8 (1st June 2020) - Deng, Junyi; Ma, Kaihui; Hu, Liwen; Kou, Mingyin; Wen, Liangying; Xu, Jian
Abstract: Wustite (FeO)-centered multicomponent oxides play an important role in the ironmaking process, and a complete understanding of their high temperature behaviors is of great importance for process optimization to achieve high efficiency and low emissions during industrial production. In this work, the transient shrinkages of FeO-centered multicomponent oxide packed beds are quantitatively determined in a reducing atmosphere up to 1773 K, and the effects of the interactions between the oxides on the shrinkage rate (SR) are qualitatively evaluated. The results show that although mixing CaO with FeO increases the SR to 0.42%/K below 1173 K, further mixing with SiO2 or Al2 O3 significantly limits this enhancement effect due to the formation of an olivine or spinel phase. However, in the subsequent stage, the SR increases to as high as 0.44%/K after CO is injected. The interaction between FeO and MgO leads to an SR of greater than 0.20%/K at lower temperatures, but it causes a decrease in the SR from 0.33%/K to 0.16%/K between 1173 K and 1273 K. Meanwhile, adding SiO2 slows the reduction reaction, and the SR correspondingly decreases further to 0.04%/K. On the other hand, the interaction between CaO and Al2 O3 takes precedence over the interaction between SiO2 and MgO and dominates the shrinkage process in the quinary-component case, and the preferentially formed CaAl2 O4 spinel phase hinders the formation of the Mg2 SiO4 olivine phase.